Low-Level Social Demand Is Associated with Anxiety-Related Gamma Wave Responses in Autistic Male Youth - Vicki Bitsika; Christopher F. Sharpley; Ian D. Evans; Christopher B. Watson; Rebecca J. Williams; Kirstan A. Vessey (Brain Sciences, 2025)
Background: The Autism Spectrum Disorder (ASD) characteristic of difficulties in social communication and interaction has been previously associated with elevated anxiety and the degree of mental effort required to understand and respond to social cues. These associations have implications for the mental health of autistic youth, but they are usually based on correlational statistics between measures of anxiety and social interaction demands that are collected in formal psychological testing settings. Another index of mental effort that has been found to correlate with anxious arousal is gamma wave activity, which is measured via EEG. Methods: To compare data from both of these indicators of mental effort and anxiety, a two-stage study was conducted using (1) standardized test data and (2) in vivo EEG data in a low-demand social setting. Results: As well as significant associations between social cognition and anxiety from standardized scales, there were also meaningful relationships between social cognition and gamma wave activity. Conclusions: Because gamma wave activity represents the highest level of cognitive complexity for brain activity, is an index of hypervigilance under threatening conditions, and has been associated with anxiety in autistic youth, these findings suggest that even low-level demand social interaction settings may initiate high-level anxiety-related behaviour in autistic youth.